Eksistensi Peraturan Walikota Nomor 39 Tahun 2017 Tentang Tes Urine Pranikah di Kota Binjai Ditinjau Dari Maqāṣid Asy-Syarī’ah - M Prayuda Aprian (Jurnal Penelitian Medan Agama, 2020)
The current phenomenon, many Indonesian people, especially in the city of Binjai, ended their household ark with divorce, one of which was drug. Then the mayor issued a regulation that is the mayor regulation number 39 of 2017. One of the contents is a prenuptial urine test as a requirement to get a control card / NA. Every rule / policy issued certainly has a purpose. Then Islam has rules (Shari'at) which aim to produce benefits and reject mafsadat. as for the benefits to safeguard religion, self, reason, descent and wealth. This study aims to determine the purpose of shari'ah (maqāṣid asy-syarī’ah) towards the mayor's regulation number 39 of 2017 concerning premarital urine tests in the city of Binjai. The application of the mayor's regulations has resulted in the benefit of the Binjai community in safeguarding religion, self, reason, descent, and property. Then the general goal of the mayor's regulation is to map which areas are high in drug users. Whereas the review of maqāṣid asy-syarī'ah is to safeguard religion, self, reason, descent and wealth.